2012
DOI: 10.2139/ssrn.2071615
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Performance of Islamic and Conventional Banks 2004 to 2009

Abstract: We compare, using data envelopment analysis (DEA) and meta-frontier analysis (MFA), the performance of Islamic and conventional banks during the period [2004][2005][2006][2007][2008][2009]. The use of nonparametric MFA is new to the Islamic banking context. Our DEA finds no significant difference in mean efficiency between conventional and Islamic banks when efficiency is measured relative to a common frontier. The MFA however, reveals some fundamental differences between the two bank types. In particular, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 11 publications
(14 reference statements)
3
49
1
Order By: Relevance
“…Yet the Islamic banking system, due to constraints imposed by Shariah law, is less efficient than the conventional one (Johnes et al 2014;Abdul-Majid et al 2010) 4 Empirical results…”
Section: Preliminary Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Yet the Islamic banking system, due to constraints imposed by Shariah law, is less efficient than the conventional one (Johnes et al 2014;Abdul-Majid et al 2010) 4 Empirical results…”
Section: Preliminary Data Analysismentioning
confidence: 99%
“…The previous studies find that the Islamic banks are less cost efficient than the conventional banks (see Ahmad et al 1998). Newer empirical evidence suggests that the human capital investments on behalf of the Islamic banks have been paying off as they contribute toward closing the gap in managerial inadequacies (Johnes et al 2014). The higher liquidity, as represented by liquid assets/deposits, has a favorable effect on both types of banks.…”
Section: Conditional Survival Function Estimatesmentioning
confidence: 99%
“…Hughes et al (1994) suggest that, under the assumption of risk aversion, managers are willing to give up part of their compensations in favour of risk reduction. Miller and Noulas (1997) notice that an increase in credit risk leads to an improvement in profit margin, leading subsequently to an enhancement of efficiency (Johnes et al, 2013). Among the studies that corroborate a positive relationship between efficiency and risk we mention those of Altunbas et al (2007), Yener et al (2007), Yong and Christos (2013) and Saeed and Izzeldin (2014).…”
Section: Literature Reviewmentioning
confidence: 94%
“…These hypotheses represent the relationship between cost and revenue efficiency and risk, capital, size, and market structure. Gorton and Rosen (1995), Hughes et al (1994), Miller and Noulas (1997), Altunbas et al (2007), Yener et al (2007), Yong and Christos (2013), Johnes et al (2013), Saeed and Izzeldin (2014).…”
Section: The Hypothesesmentioning
confidence: 99%
“…This location inside the frontier reveals that the IBs system is less competent during the comparison to CBs. Johnes, Izzeldin & Pappas (2012); Majid (2005) and Bhattacharyya et al (2010) found an amount of reasons for estimating the lower performance of IBs than Non-Islamic banks (N-IB). First of all, because of stringent Shariah rules and restrictions which limits products are not being standardized and then the consequence is enhanced operational cost in comparison to N-IB.…”
Section: Introductionmentioning
confidence: 99%